2001
DOI: 10.1089/089277901750134548
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stone Analysis in Metabolic Evaluation and Medical Treatment of Nephrolithiasis

Abstract: Compositional stone analysis should be an integral part of the metabolic evaluation of patients with nephrolithiasis. Moreover, stone analysis alone may provide guidance for therapeutic treatment and obviate a formal metabolic evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 19 publications
1
42
0
6
Order By: Relevance
“…[2,14] Variation in composition of stone from initial sample may occur over time, and subsequent stone may be of still another composition; therefore, analysis should be repeated in recurrent cases. [15,16] Stone analysis can reveal risk factors for stone disease, as well as identify treatment targeted to prevent stone formation or dissolve an existing stone (litholysis). [10] Stones containing brushite (CaHPO 4 .2H 2 O), uric acid, and urate signal high risk for recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[2,14] Variation in composition of stone from initial sample may occur over time, and subsequent stone may be of still another composition; therefore, analysis should be repeated in recurrent cases. [15,16] Stone analysis can reveal risk factors for stone disease, as well as identify treatment targeted to prevent stone formation or dissolve an existing stone (litholysis). [10] Stones containing brushite (CaHPO 4 .2H 2 O), uric acid, and urate signal high risk for recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Stone analysis is warranted in all patients and may provide guidance for the therapeutic treatment. Kourambas et al [17] stated that non calcareous stone forming patients reflected specific metabolic disorders. The authors suggested that compositional stone analysis should be an integral part of the metabolic evaluation of patients with nephrolithiasis and stone analysis alone may provide guidance for therapeutic treatment and obviate a formal metabolic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Medical treatment, metaflaxi and modifications in dietary habits can help to prevent recurrence of urinary stones. Medical treatment should be based on assessing 24h urinary metabolic abnormalities (13). Drug treatment is advised after a high fluid intake (>3 L/day).…”
Section: Discussionmentioning
confidence: 99%